2015
DOI: 10.1007/s00296-015-3379-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of interleukin-1 beta can predict response to tocilizumab therapy in rheumatoid arthritis: the PETITE (predictors of effectiveness of tocilizumab therapy) study

Abstract: Predicting the responses of patients with rheumatoid arthritis (RA) to tocilizumab is difficult, because inflammatory markers such as C-reactive protein rapidly normalize regardless of clinical efficacy. We aimed to identify factors that could predict response to tocilizumab. Sixty-five patients completed 52 weeks of tocilizumab therapy. Serum fibrinogen, D-dimer and interleukin (IL)-1β levels were measured at baseline and after 4 weeks of therapy. Clinical responses to tocilizumab were assessed using disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…77 Other relatively small studies suggested baseline serum IL-6 receptor levels as a predictor of clinical remission at week 24 78 and serum levels of IL-1b and D-dimer at 4 weeks after treatment as predictors of response at week 52. 79 High baseline natural killer cell numbers were also associated with remission after 3 months of tocilizumab therapy. 80 All these studies need to be confirmed in independent cohorts.…”
Section: Predictors Of Response To Tocilizumab Treatmentmentioning
confidence: 98%
“…77 Other relatively small studies suggested baseline serum IL-6 receptor levels as a predictor of clinical remission at week 24 78 and serum levels of IL-1b and D-dimer at 4 weeks after treatment as predictors of response at week 52. 79 High baseline natural killer cell numbers were also associated with remission after 3 months of tocilizumab therapy. 80 All these studies need to be confirmed in independent cohorts.…”
Section: Predictors Of Response To Tocilizumab Treatmentmentioning
confidence: 98%
“…In practice, lower remission rates in rheumatoid arthritis patients receiving treatments including anti-TNFα biologics are significantly associated with obesity and greater body mass index (BMI) (Levitsky et al, 2017), which are related to higher serum IL-1β concentrations (Shoda et al, 2017). The PETITE study also demonstrated that rheumatoid arthritis patients with lower baseline IL-1β concentrations significantly responded to tocilizumab compared with those with higher values (Okano et al, 2016). Therapies targeting IL-1β have been shown to reduce disease activity in rheumatoid arthritis patients refractory to anti-TNFα therapy (Cavalli & Dinarello, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have so far aimed to predict the response to tocilizumab therapy in patients with RA. Although several predictive factors were identified [14][15][16][17][18][19], including serum levels of CRP, IL-6, soluble IL-6 receptor, soluble gp130, IL-1b, and osteopontin and platelet counts, most of the studies did not focus on the response to tocilizumab monotherapy, except one study by Kojima et al [20]. They analyzed the data from their registry and showed a positive association between concomitant use of methotrexate and remission achievement by tocilizumab therapy in patients with high baseline disease activity (DAS28-ESR > 5.1), which is compatible with our results showing DAS28-ESR at baseline as a predictive factor for remission achievement in SWITCH.…”
Section: Discussionmentioning
confidence: 99%